Positive column contraction of the glow discharge in nitrogen - Lisovskiy, V.A.; Derevianko, V.A.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2017)
This paper studies the diffuse mode of the positive column in nitrogen, the contracted one near the threshold of its onset as well as the transition between these modes. The dynamics of the reduced electric field E/p variation as well as that of the electron temperature Te and the plasma concentration are investigated with a Langmuir probe in the process of this transition. The diffuse mode is observed at low pressure in the total range of discharge current values as well as at the pressure values above the threshold one of 1.5 Torr and low current values. The contracted mode sets on at the pressure values above 1.5 Torr. A jump-like transition occurs between the diffuse mode (with low E/p and Te) and the contracted one when a critical current value is attained. Исследован положительный столб в азоте в однородном режиме, в контрагированном режиме вблизи порога его появления, а также переход между этими режимами. С помощью Ленгмюровского зонда изучена динамика изменения приведенного электрического поля E/p, температуры электронов Te и плотности плазмы в процессе данного перехода. Диффузный режим наблюдается при низких давлениях во всём диапазоне разрядных токов, а также при давлениях выше порогового 1,5 Toрр и низких токах. Контрагированный режим появляется при давлениях выше 1,5 Toрр. Между диффузным режимом (с низкими E/p и Te) и контрагированным (с высокими E/p и Te) при достижении критического тока происходит скачкообразный переход. Досліджено позитивний стовп в азоті в однорідному режимі, в контрагованому режимі поблизу порога його виникнення, а також перехід між цими режимами. За допомогою Ленгмюрівського зонда вивчена динаміка зміни зведеного електричного поля E/p, температури електронів Te і густини плазми в процесі цього переходу. Дифузний (однорідний) режим спостерігається при низькому тиску у всьому діапазоні розрядного струму, а також при тиску вище порогового 1,5 Toрр і низькому струмі. Контрагований режим з'являється при тиску вище 1,5 Toрр. Між дифузним режимом (з низькими E/p і Te) і контрагованим (з високими E/p і Te) при досягненні критичного струму відбувається стрибкоподібний перехід.